Colonial Legacy and Strategic HRM in Indonesia's Civil Service: A Southeast Asian Comparison - Johanna Novita; Harry Nenobais; Sri Lalanawati Octaviani (Darul Yasin Al Sys, 2026)
Bureaucratic reform in Indonesia has substantially modernized administrative procedures; however, improvements in bureaucratic performance remain uneven, suggesting that procedural reform alone cannot resolve persistent institutional constraints. This study aimed to examine the configuration of public-sector human resource management in Indonesia through a comparative analysis of five Southeast Asian administrative systems: Hong Kong, Macau, Malaysia, Thailand, and the Philippines. A qualitative comparative approach was employed using document analysis guided by Berman’s Strategic Human Resource Management framework and historical institutionalism. The findings indicate that Indonesia has achieved considerable procedural modernization in merit-based recruitment through the Computer Assisted Test (CAT), but these advances have not been consistently sustained in bureaucratic neutrality and performance-based compensation. The analysis identifies a pattern of asymmetrical strategic alignment in which recruitment reforms coexist with persistent organizational and institutional constraints across subsequent stages of the civil service career cycle. These constraints are rooted in historically embedded administrative routines that continue to shape authority relations, personnel management, and performance governance. The study extends Strategic Human Resource Management by demonstrating that strategic alignment is institutionally contingent rather than determined solely by the coherence of human resource policies. It concludes that sustainable civil service reform requires institutional transformation beyond procedural modernization, particularly through stronger merit-system governance, enhanced protection of bureaucratic neutrality, and the redesign of performance management toward outcome-oriented evaluation. These findings provide a comparative framework for understanding civil service reform and offer practical guidance for strengthening public-sector human resource governance in Indonesia.